PENDAMPINGAN KONSELING PADA REMAJA MELAKUKAN SELF HARM - Rohimah, Siti; Fatiyatus, Siti; Msarujahid, Kasori; Citrasari, Novenna; WIjaya, Muria (Jurnal Manajemen Pendidikan, 2025)
Many phenomena of self-harm lately have occurred in the lives of adolescents when adolescents are unable to deal with disappointment, sadness and anger. This research uses a qualitative research method with the "Life History" method approach is used as a method that aims to reveal parenting patterns, causes, triggering factors, the process of self-harm, and strategies to stay away from four teenage students who do self-harm. This research shows that there are some differences and similarities between the perpetrators with each other in terms of parenting patterns, ways of doing self-harm, current conditions, and strategies for letting go of self-harm habits. The cause of adolescents doing self-harm in this study is their parenting style with a background of harsh upbringing, lack of appreciation, anger, comparisons with others, and physical violence, even though there are other parents who are very academically supportive. and non-academic children. Friendship and love problems are another cause for adolescents to self-harm in this study. Counseling provides effective healing for adolescents who self-harm. The approach involves emotional closeness with others, motivation for achievement, acceptance of reality, and drawing closer to God.